Construction of the Index of Social Work Professional Identity. (September 2021) - Duan, Wenjie; Li, Yumei; Kong, Yansi
Purpose: The present study applied the Dynamic Systems Model of Role Identity to construct an index of social work professional identity. Methods: The data were obtained from a longitudinal study of social work in China in 2019. Exploratory structural equation modeling and multigroup confirmatory factor analysis were used to confirm the factor structure. Independent samples t test was adopted to test the difference among different groups. Results: The four-factor (i.e., social, role, target, and action perceptions) index of social work professional identity showed acceptable reliability and good validity. Measurement invariance was observed across different groups (i.e., gender, education background, professional certification, job position, and work seniority). Differences were observed on professional identity among different genders, educational backgrounds, and professional certification groups. Conclusions: The index of social work professional identity can contribute to policymaking, educational curriculum design, and evidence-based interventions aimed at promoting professional identity.